KEPENTINGAN INDONESIA MENGIMPOR BAWANG PUTIH DARI CHINA TAHUN 2019 - Rahmi Atika Rahayu; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This This study aims to examine the Indonesia’s Interests In Importing Garlic From China 2019.. The research method used is qualitative research. This research is focused on discussing the Indonesia’s Interests In Importing Garlic From China 2019.. Second, researchers feel the need to provide a time limit for the phenomenon or problem to be studied, namely the years 2014-2019. This research uses the theory of liberalism. This research also uses the theory of internasional cooperations and the concept of national interests which is an important discussion in this research. The research data is obtained from books, journals, official documents and website that support the hypothesis. The study concludes that the research aims to determine Indonesia's interests in importing garlic from China in 2019 and to find out the policies made by the Indonesian government in handling garlic import cases. It’s known that Indonesia's interest in importing garlic from China is because domestic supplies are only able to meet 10% of national demand. The unbalanced tendency of garlic production and consumption where consumption is higher than production, causes a production deficit that encourages imports. In addition, the high price of local garlic causes people to prefer cheaper imported garlic due to the tariff reduction policy implemented by the government. So far, the policies made by government only focused too much on import regulation. The magnitude of the government's attitude in importing garlic from China is also due to evidence that there is bribery and corruption practices from imports involving members of the Indonesian government and garlic importers. Keywords: Government Policy, National Interests, Garlic Imports